2017
DOI: 10.1371/journal.pone.0176760
|View full text |Cite
|
Sign up to set email alerts
|

Reduced cerebrospinal fluid concentration of interleukin-12/23 subunit p40 in patients with cognitive impairment

Abstract: BackgroundThe role of inflammation in Alzheimer’s disease (AD) and other cognitive disorders is unclear. In a well-defined mono-center population, we measured cytokines and chemokines in paired serum and cerebrospinal fluid (CSF) samples.MethodsConsecutive patients with AD (n = 30), stable mild cognitive impairment (SMCI, n = 11), other dementias (n = 11), and healthy controls (n = 18) were included. None of the subjects was treated with glucocorticoids, cholinesterase inhibitors, or non-steroidal anti-inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 52 publications
3
9
2
Order By: Relevance
“…Furthermore, Tat-induced expression of CCL4 and IL-17A interacted with exposure time to predict increased FST mobility after 2 weeks of exposure, while predicting a decrease after 8 weeks of Tat. The correlation of IL-12p40 and IL-17A expression in the PFC with Tat-induced dysfunctional coping aligns with previous reports indicating their importance in potentially mediating depression and cognitive impairment and suggest they might be therapeutic targets for HAND ( Johansson et al, 2017 ; McGeachy et al, 2019 ). Prolonged Tat induction in the present study increased CCL5, CCL11, 1L-1β, and IL-6 levels in the striatum.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, Tat-induced expression of CCL4 and IL-17A interacted with exposure time to predict increased FST mobility after 2 weeks of exposure, while predicting a decrease after 8 weeks of Tat. The correlation of IL-12p40 and IL-17A expression in the PFC with Tat-induced dysfunctional coping aligns with previous reports indicating their importance in potentially mediating depression and cognitive impairment and suggest they might be therapeutic targets for HAND ( Johansson et al, 2017 ; McGeachy et al, 2019 ). Prolonged Tat induction in the present study increased CCL5, CCL11, 1L-1β, and IL-6 levels in the striatum.…”
Section: Discussionsupporting
confidence: 89%
“…It is not known if this is consistent in the brain, but it was demonstrated in other mouse models that inhibition of IL-12/23 p40 was associated with reduced Aβ levels 57 , 58 . This seems to agree with a recent small scale study using CSF from human participants that showed a positive correlation of IL-12/23 p40 with CSF Aβ1-42 59 , and our own current work here. This evidence strengthens the connection between brain amyloid load and the immune system.…”
Section: Discussionsupporting
confidence: 94%
“…In concur with other recent works which presented evidences of histone deacetylase-2 as player in stress-induced cognitive impairment via histone deacetylation and PI3K/AKT pathway modulation ( Verma et al, 2017 ; Wu et al, 2017 ), our results are consent with these published studies. However, the recognized biological processes leading to the pathogenesis of POCD, such as inflammation, stress, and apoptosis ( Tian et al, 2015 ; Johansson et al, 2017 ; Zhang et al, 2018 ), are less prominent in our results. Sirtuin1 (SIRT1) is a deacetylase protein that reported to mediate hippocampal neuronal apoptosis in mice and causing cognitive deficit ( Min et al, 2018 ).…”
Section: Discussioncontrasting
confidence: 80%
“… Yi et al (2015) reported the close relatedness of inflammatory response with the changes in cognitive function in cardiopulmonary bypass patients ( Yi et al, 2015 ). In a similar manner, interleukin-12 and its receptor were demonstrated to influence cognitive function ( Johansson et al, 2017 ; Vonder Haar et al, 2017 ; Wu et al, 2017 ). Likewise, cytokines and cytokines receptor participate apoptosis and immune regulation through Jak-STAT signaling pathway by specifically activate STAT4 ( Darnell et al, 1994 ; Kang and Kang, 2008 ).…”
Section: Discussionmentioning
confidence: 83%